ANALYSIS OF ACUTE MYELOID LEUKEMIA IN SHOWA UNIVERSITY HOSPITAL IN PAST TEN YEARS - FUJIWARA, Shun; TSUKAMOTO, Hiroyuki; SAITO, Bungo; HATTORI, Norimichi; ARAI, Nana; NAKAMAKI, Tsuyoshi; WATANUKI, Megumi; YANAGISAWA, Kouji (Journal of The Showa University Society, 2020)
We retrospectively analyzed the pathology and prognosis of 111 pts with acute myeloid leukemia （AML） in the past 10 years in the Showa University Hospital; 52.2％ of the patients was over 65 years old and 28.8％ had a diagnosis of AML with MRC. Overall survival （OS） was 34.5％ and median survival time was 22 months. Multivariate analysis showed that age and gender significantly influenced OS of patients. Except for t（15；17）, the significance of karyotype was limited. SCT did not significantly improve OS of AML. Introduction of a further targeted therapy based on the molecular pathology and a decrease non-relapse mortality in SCT appeared to be important to improve survival of AML of high age elderly.